Adaptation of myocardial blood flow to increased metabolic demand is not dependent on endothelial vasodilators in the rat heart. Issue 2 (February 1997) - Tiefenbacher, C. P.; Tillmanns, H.; Niroomand, F.; Zimmermann, R.; Kübler, W.
Abstract : OBJECTIVE: To investigate the role of endothelial vasodilating factors in adaptation of myocardial blood flow to increased metabolic demands. DESIGN: Alterations in the effects of endothelium dependent (acetylcholine) and independent (sodium nitroprusside) vasodilators and the beta 1 receptor agonist dobutamine were studied after inhibition of endothelium derived relaxing factor (EDRF) with L-NG-nitro-arginine methyl ester (L-NAME), prostanoid synthesis with indomethacin, and ATP sensitive potassium channels with glibenclamide. EXPERIMENTAL ANIMALS: Female Wistar rats, in situ perfused heart. MAIN OUTCOME MEASURES: Myocardial blood flow (H2 clearance); systolic fractional thickening (pulsed Doppler); mean arterial blood pressure. RESULTS: L-NAME reduced myocardial blood flow by 58 (12)% (mean (SD), P < 0.001) and systolic thickening fraction (FT) by 36 (9)% (P < 0.05). These effects were significantly reversed by administration of L-arginine but not D-arginine. Pretreatment with L-NAME inhibited the increase in myocardial blood flow caused by acetylcholine (control: +42 (9)%; L-NAME: -29 (7)%, P < 0.001) but did not affect the increase in myocardial blood flow caused by sodium nitroprusside (control: +44 (5)%; L-NAME: +34 (10)%, NS). Pretreatment with L-NAME did not change the effect of dobutamine on myocardial blood flow (+61 (3)%) and FT (+32 (8)%) compared with baseline values (P < 0.001). Neither pretreatment with indomethacin nor with glibenclamide reduced the dobutamine induced increase in myocardial blood flow. CONCLUSIONS: Inhibition of EDRF, prostanoid synthesis, and ATP sensitive potassium channels did not reduce the vasodilator reserve during increased metabolic demands induced by beta 1 adrenergic stimulation. Therefore, adaptation of myocardial blood flow to increased metabolic demands is independent of endothelial relaxing factors in the rat heart.